Influence Of Pesticides on Some Morpho-Biochemical Parameters of Liver Microsomes of Pregnant Rats and Their Embryos - Tuychieva, Dilfuza; Mirkhamidova, Parida; Shakhmurova, Gulnara; Alimova, Rano; Mukhamedov, Gafurzhon (Journal of Neonatal Surgery, 2025)
Poisoning of animals with pesticides - butylcaptax and Dropp causes pronounced dystrophic processes at the level of cells and subcellular structures of the liver. Along with slightly changed cells, there are heavily damaged ones. When inoculating pregnant rats with butylcaptax and Dropp, we found that in the liver microsomes of pregnant rats and their embryos, there is a tendency to a decrease in the content of PC, PE and the amount of phospholipids. In microsomal fractions, the level of LPL, FA and the ratio of CS / PL increases. However, these changes are more pronounced in poisoning on the 19th day of pregnancy, especially in experiments with butylcaptax. The results of studying the effect of butylcaptax and Dropp on the level of malondialdehyde showed that it leads to intensification of NADPH and ascorbate-dependent lipid peroxidation in the liver microsomes of the fetus and mother. The highest level of MDA with the introduction of butylcaptax and Dropp is in non-enzymatic lipid peroxidation. The content of cytochrome P-450 in microsomes is noted in case of poisoning with butyl captax on the 3rd day of pregnancy; the microsomal fractions of the liver of pregnant rats decrease. A more pronounced decrease in the content of this enzyme is observed in case of poisoning with butyl captax on the 3rd and 19th days of pregnancy